1984
DOI: 10.1161/01.res.54.6.674
|View full text |Cite
|
Sign up to set email alerts
|

Carotid sinus baroreceptor reflex control and the role of autoregulation in the systemic and pulmonary arterial pressure-flow relationships of the dog.

Abstract: To understand more fully the role of the arterial baroreceptor reflex on systemic and pulmonary vascular resistance, we studied the influence of the carotid sinus baroreceptor reflex control system on the entire systemic and pulmonary arterial pressure-flow relationships. Ten pentobarbital-anesthetized dogs, whose carotid sinuses were isolated, were used in a preparation in which the right and left hearts were bypassed to control systemic and pulmonary blood flows. At intrasinus pressures of 50, 125, and 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Shoukas et al 10 have reported that large changes in carotid sinus pressure may produce small shifts in the pulmonary vascular pressure-flow relationship. The changes in blood pressure that we observed after opening the fistulas in each condition or after hydralazine therapy were small, and would not be expected to have altered the PA-CO plots.…”
Section: Discussionmentioning
confidence: 99%
“…Shoukas et al 10 have reported that large changes in carotid sinus pressure may produce small shifts in the pulmonary vascular pressure-flow relationship. The changes in blood pressure that we observed after opening the fistulas in each condition or after hydralazine therapy were small, and would not be expected to have altered the PA-CO plots.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence primarily derived from animal experiments suggests that the carotid sinus baroreflex also affects respiratory function (7,26,45,48). Rapidly increasing blood pressure causes decreased ventilation, whereas decreasing blood pressure causes increased ventilation.…”
Section: Baroreceptors; Ventilation; Blood Pressurementioning
confidence: 99%
“…Some factors, such as catecholamines, which can modify Q, may also act on HPV [24]. However, although no catecholamines were used in this study, no variations in fC or SAP were found before or after dextran infusion.…”
Section: Discussionmentioning
confidence: 81%